ChemInform Abstract: ZrCl4 as a New Catalyst for Ester Amidation: An Efficient Synthesis of h‐P2X7R Antagonists. Issue 27 (16th June 2016) - Homerin, Germain; Baudelet, Davy; Dufrenoy, Pierrick; Rigo, Benoit; Lipka, Emmanuelle; Dezitter, Xavier; Furman, Christophe; Millet, Regis; Ghinet, Alina
Abstract: It is shown that the catalytic activity of ZrCl4 is higher for the amidation of methyl‐pyroglutamate derivatives compared to conventional catalysts (PTSA or HCl).